Thalassemic erythrocytes inhibit in vitro growth of Plasmodium falciparum - C. R. Brockelman (2018)
Blood specimens from 100 thalassemic patients were screened in vitro for inhibitory effects on growth and multiplication of Plasmodium falciparum. The culture medium mixture designated REM consisted of 9 volumes of minimum essential medium (GIBCO Laboratories, Grand Island, N.Y.) and 1 volume of RPMI 1640 (GIBCO) supplemented with 10% heat-inactivated human serum. Parasite multiplication in erythrocytes containing normal hemoglobin cultured in RPMI or REM was similar. Significant reduction in parasite multiplication rates was observed in erythrocytes containing abnormal hemoglobin when these were cultured in REM. The degree of reduction in five types of thalassemic erythrocytes was in the following descending order: hemoglobin H disease with Hb Constant Spring, classical hemoglobin H disease, β 0 -thalassemia-hemoglobin E in which blood harbored a high percentage of hemoglobin F-containing cells, β 0 -thalassemia-hemoglobin E in which blood harbored few hemoglobin F-containing cells, and β-thalassemia heterozygous variant.